ISTL is Still Exceptional, in More Ways Than One - David Flaxbart (Issues in Science and Technology Librarianship)
A former editorial board member (Viewpoints Editor, 2000-2020; Refereed Articles Editor, 2016-2018) looks back on two decades of board membership, and discusses trends in Open Access (OA) publishing in STEM librarianship. Journals like ISTL are still the exception rather than the norm.